Double-Stranded RNA Derived from Lactic Acid Bacteria Augments Th1 Immunity via Interferon-β from Human Dendritic Cells - Kawashima, Tadaomi; Ikari, Naho; Watanabe, Yohei; Kubota, Yoshiro; Yoshio, Sachiyo; Kanto, Tatsuya; Motohashi, Shinichiro; Shimojo, Naoki; Tsuji, Noriko M. (Frontiers in Immunology, 2018)
Lactic acid bacteria (LAB) are one of the major commensal species in the small intestine and known for contributing to maintenance of protective immunity and immune homeostasis. However, currently there has been no evidence regarding the cellular mechanisms involved in the probiotic effects of LAB on human immune cells. Here, we demonstrated that LAB double-stranded RNA (dsRNA) triggered interferon-β (IFN-β) production by human dendritic cells (DCs), which activated IFN-γ-producing T cells. Interleukin-12 (IL-12) secretion from human DCs in response to LAB was abrogated by depletion of bacterial dsRNA, and was attenuated by neutralizing IFN-β, indicating LAB dsRNA primarily activated the IFN-β/IL-12 pathway. Moreover, the induction of IL-12 secretion from DCs by LAB was abolished by the inhibition of endosomal acidification, confirming the critical role of the endosomal digestion of LAB. In a co-culture of human naïve CD4+ T cells and BDCA1+ DCs, DCs stimulated with LAB including dsRNA induced IFN-γ-producing T cells. These results indicate that human DCs activated by LAB enhance Th1 immunity depending on IFN-β secretion in response to bacterial dsRNA.